Unraveling the Complex Policies Regulating Conflicts of Interest and Criminal Corruption - Wedha, Yogi Yasa; I Made Hendra wijaya; Hudali Mukti; Turymshayeva , Arida (Lembaga Contrarius Indonesia, 2025)
Corruption is significantly influenced by conflicts of interest in a variety of industries. Indonesia has implemented a variety of regulations to prevent corruption and conflicts of interest. Nevertheless, its implementation continues to encounter a variety of obstacles. This investigation aims to evaluate the intricacy of policies that regulate conflicts of interest and corruption and investigate strategies that can enhance the efficacy of corruption prevention and eradication in Indonesia. The research method employed is normative juridical, incorporating a conceptual approach, legislation, and comparative studies with Kazakhstan, which has a more stringent anti-corruption legal system. The study's findings indicate that Indonesia has implemented numerous regulations prohibiting corruption and conflicts of interest. However, there is a lack of transparency in decision-making, poor law enforcement, weak coordination between institutions, and disharmony between regulations. In contrast, Kazakhstan implements more stringent sanctions, centralized institutions, and regulations. A comprehensive approach to the prevention of conflicts of interest and malfeasance necessitates the optimization of legal substance, legal structure, and legal culture. The following strategies must be implemented: the development of clear regulations, the enforcement of stringent laws, the enhancement of transparency and accountability, and the protection of whistleblowers. To guarantee transparency, integrity, and pure governance in Indonesia, it is imperative to implement more comprehensive policy reforms that are not solely based on legal requirements but also consider social and cultural factors.